2003
DOI: 10.1152/ajpcell.00052.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress remodels expression and function of junctional proteins in cultured bone cells

Abstract: 2 for 1-3 h. Immunostaining indicated that at 5 dyn/cm 2 , the distribution of Cx43, Cx45, and ZO-1 was moderately disrupted at cell membranes; at 20 dyn/cm 2 , disruption was more severe. Intercellular coupling was significantly decreased at both shear stress levels. Western blots showed the downregulation of membrane-bound Cx43 and ZO-1 and the upregulation of cytosolic Cx43 and Cx45 at different levels of shear stress. Similarly, Northern blots revealed that expression of Cx43, Cx45, and ZO-1 was selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 64 publications
(83 reference statements)
1
75
0
Order By: Relevance
“…These results suggest that HSSGs play only a secondary role in the reorganization of actin filaments and their associated linker protein vinculin. Previous studies (17,21) have shown that ZO-1 and Cx43 expression is sensitive to fluid shear stress in USS and HSSG regions, because stable junctions are not able to form. Recent studies suggest that, in addition to organizing TJ proteins, such as occludin and ZO-2, and enabling Cx43 to dock at the cell surface, ZO-1 serves as a linker between TJ proteins and F-actin (39,40).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results suggest that HSSGs play only a secondary role in the reorganization of actin filaments and their associated linker protein vinculin. Previous studies (17,21) have shown that ZO-1 and Cx43 expression is sensitive to fluid shear stress in USS and HSSG regions, because stable junctions are not able to form. Recent studies suggest that, in addition to organizing TJ proteins, such as occludin and ZO-2, and enabling Cx43 to dock at the cell surface, ZO-1 serves as a linker between TJ proteins and F-actin (39,40).…”
Section: Discussionmentioning
confidence: 93%
“…To detect the changes in stress fibers (SFs) and dense peripheral actin bands (DPABs) [F-actin rhodamine-labeled phalloidin (Sigma)], focal adhesions (FAs) [Vinculin and Paxillin (Chemicon)], and tight junction [TJ; ZO-1 (Zymed)] and gap junction complexes (Cx43, courtesy of E. Hertzberg, Albert Einstein College of Medicine), immunofluorescence analyses were performed on both controls and shear stress-exposed cells (21). Fifteen milliunits per milliliter of heparinase III (Sigma) was used to digest the glycocalyx (11), and HSPG antibody (US Biological, Swampscott, MA) and CellTracker orange (Molecular Probes) were used to assess heparan sulfate removal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opening of membrane channels for the passage of signaling molecules initiated by pN-level forces is detectable by whole-cell patch-clamp electrophysiology with high temporal resolution. Previous culture studies have shown that networks of osteocytes respond to forces imposed by fluid shear stress and substrate stretching, as well as to cell indentation of a much higher magnitude, with the release of nucleotides, prostaglandin E2 (PGE2), and nitric oxide (NO) into the extracellular space and elevated intercellular Ca 2+ levels owing to receptor activation (20)(21)(22)(23)(24)(25). The osteocyte mechanotransducer is likely a protein complex that includes integrins, pannexin, or connexin hemichannels (21,(26)(27)(28)(29) in addition to ligand-gated receptors, particularly purinergic receptors (30,31) and hormone receptors (32).…”
Section: Discussionmentioning
confidence: 99%
“…65 Many researcher have suggested that fluid flow induced shear stress is the primary mechanism of informing bone cells of loading conditions (osteocytes and osteoclasts more than osteoblasts). 66,67 Fluid flow also induces an electric field from movement of charged particles. Osteoclasts have been shown to migrate and act based on electrical charges caused by these fluid flows as well.…”
Section: Bone Mechanics and Mechanobiologymentioning
confidence: 99%